2004
DOI: 10.1023/b:brea.0000019961.59306.f6
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Disrupts Chemokine-Mediated Chemokine Release from Mammary Cells: Implications for the Interplay between Estrogen and IP-10 in the Regulation of Mammary Tumor Formation

Abstract: Chemokines are pro-inflammatory cytokines that function to attract immune cells to the sites of tissue inflammation, injury or infection. We have formulated the hypothesis that release of one chemokine can serve, in a local paracrine or endocrine fashion, to induce the release of other chemokines from neighboring mammary cells. We set out to investigate whether specific chemokines could promote the release of other chemokine members from mammary cells, and whether estrogen could serve to disrupt the release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…A previous HIV-1 infectivity study using primary human MEC also reported CD4 mRNA transcripts by use of PCR, as well as "faint" expression of CD4 and GalCer on MEC membranes by use of a radiobinding assay (40). While expression of CCR5 and CXCR4 was not evaluated in the report by Toniolo et al, our findings are consistent with studies of murine mammary cells, which have been found to express CCR5 and CXCR4 (2). In addition, breast cancer studies have demonstrated the presence of CXCR4 in human mammary tissue by use of immunohistochemistry (31).…”
Section: Discussionsupporting
confidence: 90%
“…A previous HIV-1 infectivity study using primary human MEC also reported CD4 mRNA transcripts by use of PCR, as well as "faint" expression of CD4 and GalCer on MEC membranes by use of a radiobinding assay (40). While expression of CCR5 and CXCR4 was not evaluated in the report by Toniolo et al, our findings are consistent with studies of murine mammary cells, which have been found to express CCR5 and CXCR4 (2). In addition, breast cancer studies have demonstrated the presence of CXCR4 in human mammary tissue by use of immunohistochemistry (31).…”
Section: Discussionsupporting
confidence: 90%
“…Ras drives cytokine secretion (36, 37, 51); thus, Let7 repression would feed forward to upregulate Ras and drive further IL6, IL8, and IP10 expression (19). IP10 upregulates CCL2 (51) and CCL2, in turn, stimulates CCL5 production by breast cancer cells (8); thus, coordinated upregulation of IP10, IL6, IL8, CCL2, and CCL5 following cancer cell invasion into fat would generate a self-perpetuating mechanism to support CSC expansion and metastasis even after cancer cell egress to other sites. Finally, coculture and cytokine exposures all upregulated c-Myc, potentially due to IL6-, IP10-, and CCL5-dependent suppression of miRs 34c-3p and/or 34-b, which target c-MYC, and also due to miR-302b-dependent c-MYC induction.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of EBV antigens in NPC tumor cells provide the targets for adoptive immunotherapy. [3][4][5][6] However, the poorly differentiated NPC is always characterized by the presence of a highly cellular lymphoid stroma admixed with tumor cells. 7 However, the role of local immunity surrounding NPC cells and the role EBV and viral products expressed in tumor cell remain unclear, which is associated with the expression of immune-related molecules including chemokines and receptors, HLA class I and II antigens, and co-stimulatory molecules and the role of EBV and viral products to alter the expression of immune-related molecules on tumor cells.…”
Section: Introductionmentioning
confidence: 99%